2009
DOI: 10.1002/term.154
|View full text |Cite
|
Sign up to set email alerts
|

Laminin and fibronectin scaffolds enhance neural stem cell transplantation into the injured brain

Abstract: Cell transplantation offers the potential to treat central nervous system injuries, largely because multiple mechanisms can be targeted in a sustained fashion. It is crucial that cells are transplanted into an environment that is favourable for extended survival and integration within the host tissue. Given the success of using fetal tissue grafts for traumatic brain injury, it may be beneficial to mimic key aspects of these grafts (e.g. three-dimensionality, cell-cell and cell-matrix support) to deliver cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
128
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(130 citation statements)
references
References 39 publications
1
128
0
1
Order By: Relevance
“…However, what is unclear is which of these environments is more conducive for cell transplant survival. Within a different post-injury environment, published studies using cell sources ranging from embryonic murine (Boockvar et al, 2005;Hoane et al, 2004;Philips et al, 2001;Riess et al, 2002;Wallenquist et al, 2009), or fetal stem cell lines (Hagan et al, 2003;Shear et al, 2004;Tate et al, 2002Tate et al, , 2009Wennersten et al, 2004), to bone marrow cells (Mahmood et al, 2001a(Mahmood et al, , 2001b(Mahmood et al, , 2003Qu et al, 2009), have reported varying degrees of cell survival after transplantation into the injured brain, both at early and later post-injury time points. Many studies have indicated that post-injury timing and location of implantation are important factors determining the fate of transplanted NS/NPCs.…”
Section: Discussionmentioning
confidence: 99%
“…However, what is unclear is which of these environments is more conducive for cell transplant survival. Within a different post-injury environment, published studies using cell sources ranging from embryonic murine (Boockvar et al, 2005;Hoane et al, 2004;Philips et al, 2001;Riess et al, 2002;Wallenquist et al, 2009), or fetal stem cell lines (Hagan et al, 2003;Shear et al, 2004;Tate et al, 2002Tate et al, , 2009Wennersten et al, 2004), to bone marrow cells (Mahmood et al, 2001a(Mahmood et al, , 2001b(Mahmood et al, , 2003Qu et al, 2009), have reported varying degrees of cell survival after transplantation into the injured brain, both at early and later post-injury time points. Many studies have indicated that post-injury timing and location of implantation are important factors determining the fate of transplanted NS/NPCs.…”
Section: Discussionmentioning
confidence: 99%
“…As a major component of basement membrane ECM, laminin has frequently been shown to influence neurite outgrowth both in vitro [42][43][44][45] and in vivo [44,[46][47][48][49] . Laminin forms a sheetlike polymer that is best known for its critical involvement in basal membrane formation.…”
Section: Polymersmentioning
confidence: 99%
“…In some cases, there will be little or no space for the cells to divide into since the target tissue has no cavity (Darabi, et al, 2009;Laflamme, et al, 2007;Terrovitis, et al, 2008). It is no surprise that most transplanted cells die within 24 hours of transplantation (Bliss, et al, 2007;Guerette, et al, 1997;Snyder, et al, 2010;Suzuki, et al, 2004;Tate, et al, 2009;Terrovitis, et al, 2008;Zhong, et al, 2010 (Kaihara and Vacanti, 1999). The use of degradable polymer scaffolds is crucial since it provides an initial remodelable substrate for the cells, provides space for the cells to reorganize into more complicated tissues, and potentially can be designed to provide an initial template to guide subsequent structure formation (Kaihara and Vacanti, 1999).…”
Section: Challenges For Novel Stem Cell-based Therapiesmentioning
confidence: 99%